UPAYA PENGEMBANGAN POTENSI BELAJAR SISWA KELAS 5 SEKOLAH DASAR KANISIUS GENDONGAN SALATIGA MENGGUNAKAN COPERATIVE LEARNING - Junita Junita; Mawardi Mawardi (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2019)
This study was aimed at knowing the importance of applying cooperative learning models or other terms of learning in small groups. With the existence of cooperative learning, it will be easier for fifth-grade students to have discussions or interactions while doing the assignments and responsibilities given by the teacher. Cooperative learning in its application in class V SD Kanisius Gendongan Salatiga has a positive impact on students. The positive impact in question is that the application of the cooperative learning model to students is easier to follow the learning process. Students are more flexible in expressing opinions to group members and with the application of this learning model in class V students get more knowledge and information about learning. In addition to students getting information from the teacher, students also get information from peers about the material discussed. Between students in the class exchange opinions and clarify information about the learning material being discussed so that students get a lot of knowledge/information through the application of a cooperative model. With the existence of cooperative learning in SD Kanisius Gendongan Salatiga, the writer proves that its application in the learning process gives development to students. The application of forming small groups in learning in class V can be carried out effectively and efficiently.